WCS120 protein family and frost tolerance during cold acclimation, deacclimation and reacclimation of winter wheat - Vítámvás, Pavel; Prásil, Ilja Tom (Plant physiology and biochemistry, 2008)
We studied how long-term cold acclimation of winter wheat (variety Mironovskaya 808), interrupted by deacclimation and then followed by reacclimation, affected the levels of cold-induced WCS120 proteins, dry-weight content, and frost tolerance in leaves. Two experiments were performed: (1) plants undergoing long-term cold acclimation (up to 112days) were quickly deacclimated (for 5days), and then reacclimated again to cold; (2) plants vernalized for varying periods of time in an early stage of their development were, after a longer deacclimation of about 14days, exposed for the same time period to cold. Five members of the WCS120 protein family were detected and quantified by image analysis in protein gel blots (in the first experiment); as well as in two-dimensional electrophoresis gels (in the second experiment). In both experiments, partially vernalized plants, after reacclimation, re-established their frost tolerance to levels similar to plants having had the same duration of cold treatment, but without deacclimation. On the other hand, these partially and fully vernalized plants reaccumulated WCS120 proteins to lower levels than plants that were not deacclimated. Further, using a mathematical model (the peak four-parameter Weibull equation), the same type of response curve was observed during plant cold treatment not only for the level of frost tolerance, but also for dry-weight content and accumulation of WCS120 proteins, with the maximum values reached at about the same time as vernalization saturation.
Keywords: Electrophoresis, Polyacrylamide Gel; Plant Leaves; Plant Proteins; elektroforéza; aklimatizace; Triticum; nízká teplota; DNA-Binding Proteins; Electrophoresis; zmrazování; pšenice; Acclimatization; elektroforéza v polyakrylamidovém gelu; rostlinné proteiny; DNA vazebné proteiny; listy rostlin; Freezing; Cold Temperature